Welding Parameter Variation on Aluminum Mechanical Properties: Pengaruh Variasi Parameter Pengelasan terhadap Sifat Mekanik Aluminium - Alvian, Arya Hardi; Mulyadi (Indonesian Journal of Innovation Studies, 2025)
General Background Welding plays a critical role in manufacturing processes, particularly for aluminum materials widely used due to their lightweight and corrosion resistance. Specific Background Variations in welding parameters such as current, voltage, and joint configuration can significantly alter mechanical properties and microstructural characteristics. Knowledge Gap Previous studies have examined welding parameters, yet limited analysis integrates multiple variables with detailed mechanical and microstructural evaluation. Aims This study aims to analyze the effect of welding parameter variations on tensile strength, hardness, and microstructure of aluminum joints. Results The findings indicate that parameter variations lead to differences in mechanical performance and microstructural formation, with certain conditions producing more stable joint characteristics. Novelty This study provides a combined evaluation of welding parameters and their relationship with mechanical and microstructural properties in a single framework. Implications The results offer practical insights for selecting appropriate welding parameters to achieve desired material performance in industrial applications. Keywords: Welding, Aluminum, Mechanical Properties, Microstructure, Parameter Variation Key Findings Highlights Parameter variation alters tensile and hardness characteristics Microstructure differences correspond to thermal input changes Certain conditions yield more stable joint performance